The Integration of Artificial Intelligence in Enhancing Students’ Digital Literacy in Plant Taxonomy Course - Gloria Sirait; Mariana Surbakti; Donni Andreas Nainggolan; Mangasi Malatua (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
This study examines the role of Artificial Intelligence (AI) technology in enhancing students’ digital literacy skills in the Plant Taxonomy course. A descriptive quantitative approach was employed using a survey method involving 32 Biology Education students at Universitas HKBP Nommensen Pematangsiantar. Data were collected through a Likert-scale questionnaire measuring AI utilization and key aspects of digital literacy, including information access, critical evaluation, data analysis, and ethical awareness. The findings reveal that students responded positively to the integration of AI in learning. AI-based applications were perceived as effective in supporting plant identification, understanding complex morphological characteristics, accelerating access to scientific references, and improving classification accuracy. Most students also demonstrated the ability to critically interpret AI-generated results, compare them with manual field observations, and use digital technology responsibly. In addition, students reported an improvement in their overall digital literacy skills after using AI in learning. In conclusion, AI technology plays a significant role in supporting interactive learning and strengthening digital literacy skills in the Plant Taxonomy course, indicating its potential for broader integration in biology education.